1987
DOI: 10.1007/bf00492471
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical procedures for the demonstration of peptide- and tyrosine hydroxylase-containing nerve fibers in cryostat sections of unfixed rapidly frozen tissue stored for long periods of time

Abstract: Traditional protocols for the immunohistochemical localization of peptides and tyrosine hydroxylase (TH) in nerve fibers in cryostat sections require the tissue to be thoroughly fixed and rinsed and to be processed for the cryostat sectioning and the immunohistochemical staining more or less directly after freezing. In the present study it was tested whether also unfixed, rapidly frozen tissue, conforming to guinea pig and bovine heart specimens, can be used for the visualization of neuropeptides [neuropeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…However, Chen et al (1998) considered that the sympathetic neurotransmission is the principal source of inhibitory neural input to the gallbladder smooth muscles, causing decreased gallbladder tone, and may contribute to the filling of the organ. In the current study TH positive nerve fibres were observed as single fibres, nerve fibres forming perivascular plexuses and nerve fibres grouped into nerve fascicles, which correlates with the results of Forsgren & Söderberg (1987) regarding the distribution of the mentioned nerves in the guinea pig and bovine heart. Our findings indicate that the nerve supply of gallbladder in swine was similar to those of guinea pig gallbladder, described by Cai & Gabella (1983).…”
Section: Discussionsupporting
confidence: 90%
“…However, Chen et al (1998) considered that the sympathetic neurotransmission is the principal source of inhibitory neural input to the gallbladder smooth muscles, causing decreased gallbladder tone, and may contribute to the filling of the organ. In the current study TH positive nerve fibres were observed as single fibres, nerve fibres forming perivascular plexuses and nerve fibres grouped into nerve fascicles, which correlates with the results of Forsgren & Söderberg (1987) regarding the distribution of the mentioned nerves in the guinea pig and bovine heart. Our findings indicate that the nerve supply of gallbladder in swine was similar to those of guinea pig gallbladder, described by Cai & Gabella (1983).…”
Section: Discussionsupporting
confidence: 90%
“…The slides were then rinsed with Tris-HCl-buffered saline (TBS, 0.05  M , pH 7.6) and fixed in acetone at –20°C for 20 min. Double staining for surface antigen CD3 and cytoplasmic antigen SP of IEL and LPL was performed by the immunofluorescence technique [38]. In brief, the bound cells were incubated with 0.5% bovine serum albumin (BSA) in TBS for 30 min to block the nonspecific staining, and then treated with rat anti-mouse CD3 mAb (50 µg/ml, KT3, MCA 500G, Serotec) in a moist chamber at 37°C for 1 h. After washing, the slides were incubated successively with 0.5% BSA for 15 min and fluorescein isothiocyanate (FITC)-labeled goat anti-rat (F(ab′) 2 fragment (30 µg/ml, Jackson ImmunoResearch Laboratories, West Grove, Pa., USA) at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were then washed in three changes of PBS, mounted in glycerol:PBS (1:1) and examined under a Leitz Orthoplane photomicroscope equipped with epifluorescence optics. For details of the immunohistochemical procedures, see also Forsgren and Söderberg [1987]. In order to enhance specific immunofluorescence reactions, treatment with acid potassium permanganate was performed for 2 min before incubation in Triton X-100 [Hansson and Forsgren, 1995].…”
Section: Immunohistochemical Proceduresmentioning
confidence: 99%